2017
DOI: 10.1017/ipm.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Are we finally making progress with suicide and self-harm? An overview of the history, epidemiology and evidence for prevention

Abstract: Ireland’s suicide rate is falling, but suicide and self-harm remain substantial societal problems. It is not possible to predict suicide at the level of the individual but good primary care, good mental health care and good social care all likely reduce risk. In terms of targeted interventions, public health measures, such as paracetamol pack size regulations, have the best evidence base to support them. Despite increased public and professional discussion, much remains to be done to provide effective, coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is important to note that in general, suicide cannot be predicted on an individual level (Large et al 2016;Chan et al 2016;Kelly, 2018) and the proportion of people with suicidal thoughts who go on to complete suicide is less than 1 in 200 (Gunnell et al 2004;Kelly, 2018). Nevertheless, the emphasis of suicide prevention strategies in Ireland on taking a multi-level, multi-strand approach (Kelly, 2018) should also include consideration of perinatal mental health factors. Jairaj et al, found that 15.8% of antenatal women in an Irish sample screened positive for depression, using an EPDS cut-off score of >12, and that these rates were highest (17.2%) in the third trimester (2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that in general, suicide cannot be predicted on an individual level (Large et al 2016;Chan et al 2016;Kelly, 2018) and the proportion of people with suicidal thoughts who go on to complete suicide is less than 1 in 200 (Gunnell et al 2004;Kelly, 2018). Nevertheless, the emphasis of suicide prevention strategies in Ireland on taking a multi-level, multi-strand approach (Kelly, 2018) should also include consideration of perinatal mental health factors. Jairaj et al, found that 15.8% of antenatal women in an Irish sample screened positive for depression, using an EPDS cut-off score of >12, and that these rates were highest (17.2%) in the third trimester (2019).…”
Section: Discussionmentioning
confidence: 99%
“…People who experience self-harm and emotional crises attend Primary Care (PC) and Emergency Department (ED) services with high frequency in many jurisdictions (Carr et al, 2016;Griffin et al, 2017;Kelly, 2017). Effective assessment and management of these presentations in the ED can be challenging due to limited resources available to meet the high demand.…”
Section: Introductionmentioning
confidence: 99%
“…Professor Brendan Kelly's editorial in IJPM June 2018 (Kelly, 2018) is a welcome historical account of the developments in suicide prevention in Ireland. He identifies the need for a coordinated, effective and compassionate approach to the problem of suicide.…”
mentioning
confidence: 99%